Pengaruh Brand Image, Promosi, dan Kepercayaan terhadap Keputusan Pembelian dalam Industri Pariwisata pada Aplikasi Traveloka: Studi Pada Masyarakat Kota Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Consumer purchasing decisions are an important factor in determining the extension of a company. A company has a good extension if it can attract consumers in deciding to purchase products from a market that gets a positive response from consumers. Brand image, promotion and trust are factors that are thought to stimulate positive emotional responses from consumers as an effort to increase consumer purchasing decisions. The aim of this research is to determine the partial and simultaneous influence of brand image, promotion and trust on purchasing decisions in the tourism industry on the Traveloka application in Denpasar City. This research was conducted in Denpasar City with a sample size of 80 people using the purposive sampling method. Primary data collection was carried out using a questionnaire. The analytical method used is multiple linear regression analysis. The results of the analysis show that 1) brand image has a positive and significant effect on purchasing decisions, 2) promotion has a positive and significant effect on purchasing decisions, 3) trust has a positive and significant effect on purchasing decisions, 4) brand image, promotion and trust have a positive and significant effect on purchasing decisions. The advice that can be given is that Traveloka is expected to maintain its characteristics and always make new innovations in creating uniqueness in the services it offers, provide attractive promos or discounts to potential users, for example bigger price discounts and provide other attractive vouchers, then be consistent in responding and handling complaints. consumers quickly and precisely without delaying or ignoring complaints submitted by consumers.